Identification of Long Non-coding and Messenger RNAs Differentially Expressed Between Primary and Metastatic Melanoma - Sun, Ledong; Guan, Zhiguang; Wei, Shanshan; Tan, Rui; Li, Pengfei; Yan, Lu (Frontiers in Genetics, 2019)
Purpose: Melanoma is the most aggressive and life-threatening cutaneous cancer. To explore new treatment strategies, it is essential to identify the mechanisms underlying melanoma tumorigenesis and metastasis. Methods: In the present study, we demonstrated altered expression of long non-coding RNA (lncRNAs) and messenger RNA (mRNA) in melanoma using data from the Cancer Genome Atlas (TCGA) database. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and protein-protein interaction analyses were conducted. We also constructed a functional lncRNA-mRNA regulatory network and Kaplan-Meier analysis. Results: We identified 246 differentially expressed (DE) lncRNAs and 856 DEmRNAs. A total of 184 DElncRNAs and 428 DEmRNAs were upregulated in metastatic melanoma, while all others were downregulated. Additionally, we investigated the co-expression pattern of 363 genes, among which 26 upregulated lncRNAs, 9 downregulated lncRNAs, 49 upregulated mRNAs and 151 downregulated mRNAs were identified as being co-expressed with others. Survival analysis suggested high levels of 14 lncRNAs and 10 mRNAs may significantly increase or decrease overall survival. These differentially expressed genes are also potentially prognostic in melanoma. Conclusions: These findings reveal potential roles for lncRNAs and mRNAs during melanoma progression and provide candidate biomarkers for future studies.